Pemetaan Daerah Potensi Rawan Longsor Kota Padang Panjang Berbasis Data Analisis Sistem Informasi Geografi (SIG) - Rahma, Anisa Lailatul; Syarief, Azhari (Al-DYAS, 2025)
This study aims to determine the level of potential landslide vulnerability and the suitability of residential land in spatial patterns for landslide vulnerability in Padang Panjang City. This study uses a quantitative descriptive method. The data analysis techniques used are scoring and overlay. The results of the study show, 1) Landslide potential areas in Padang Panjang City are dominated by high vulnerability with an area of 954.39 ha, then landslide vulnerability with a medium class of 671.16 ha, low landslide vulnerability class of 402.37 ha, and very high landslide vulnerability areas of 68.85 ha. Then seen from the residential land that is at a low vulnerability level of 390.55 ha, residential land that is at a medium vulnerability level of 52.97 ha, and residential land that is at a high vulnerability level of 0.99 ha. 2) Residential land in the spatial pattern at a low level of vulnerability is 295.47 ha, residential land in the spatial pattern at a medium level of vulnerability is 190.66 ha, residential land in the spatial pattern at a high level of vulnerability is 278.37 ha, and residential land in the spatial pattern at a very high level of vulnerability is 14.24 ha. Based on these data, it can be concluded that most of Padang Panjang City is dominated by areas with high and medium landslide potential.